The Potential Sources of Transmission and Distribution of Lymphatic Filariasis in Semarang City, Central Java, Indonesia (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2020)
Lymphatic Filariasis (LF) is a neglected tropical disease caused by filarial worms. Semarang City has an increasing number of LF. The aim of this study was to investigate potential sources of transmission and distribution of LF. It was descriptive research using cross-sectional design. The sample were 28 LF cases. The variables studied were level of knowledge, physical and biological environmental factors, and provision of health service. Data were collected with interview and observation. Data were analysed descriptively and spatially. The results showed that LF cases were distributed in centre of Semarang City, especially in the coastal area. Poor drainage and stagnant water around the houses were potential breeding places for mosquitos, which are suspected as a vector of LF transmission. Physical and biological environmental factors around the houses of LF patient may possibly be sources of distribution and transmission of LF. It was indicated with the existence of mosquito larvae in any habitats.